The Role of Organizational Culture in the Effectiveness of School Organizations - Efrita Norman; Arman Paramansyah; M Syarwani Abdan (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Organizational culture in the education system in Indonesia needs to be realized. It is intended that the next generation of the nation, especially students, grow into a generation that is smart and has the character of a leader's soul who is ready to face the challenges of life in the future. The problems above require schools to develop a school culture, such as: a culture of discipline, a sense of responsibility, honesty, sincerity, learning ethos, the habit of solving problems rationally and so on. Related to school policy means dealing with the use of resources to the results obtained. Effectiveness is the utilization of resources, funds, facilities and infrastructure in a certain amount that is consciously determined beforehand to produce a number of goods of a certain quality on time. Organizational Strategy and Organizational Culture have a complementary and reciprocal relationship in the organization's efforts to achieve its goals. Organizational culture greatly influences the organization's strategy formulation process, from strategy formulation to strategy implementation. The research method that the author takes is a literature review or literature study; which contains theories relevant to research problems. Literature review or literature study is an activity that is required in research, especially academic research whose main purpose is to develop theoretical aspects as well as aspects of practical benefits. So that by using this research method the author can easily solve the problem to be studied. The data collection method in this study was taken from data sources, which were taken from the literature of national journals. The results of the study with four literatures as references show that organizational culture plays an important role in increasing the effectiveness of school organizations and the need for organizational culture to achieve an effective school organization Keywords: Organizational Culture, Organizational Effectiveness, School Organizational Effectiveness